Pengaruh Citra Merek, Fitur, Dan Persepsi Harga Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Smartphone Xiaomi) di Kabupaten Lamongan - Ahmad Firhan Ah’sani; Hadi Purnomo (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to determine the effect of brand image, features, and price perceptions on purchasing decisions with a case study on Xiaomi smartphone consumers in Lamongan Regency. The research method used is a quantitative method with primary data through questionnaires distributed to respondents. The sampling technique in this study is the Accidental Sampling technique, which is a sampling technique based on coincidence, namely consumers who coincidentally/incidentally meet with researchers in the population, which then obtained 96 samples. The results obtained from the research conducted indicate that brand image has a negative effect on purchasing decisions, this is inversely proportional to other results that features have a positive effect on purchasing decisions, price perceptions have a positive effect on purchasing decisions. price perception has a positive effect on purchasing decisions. This study aims to determine the effect of brand image,